How Adults Ages 60+ Are Learning to Code. - Guo, Philip (Communications of the ACM, 2017)
The author discusses his project “Older Adults Learning Computer Programming: Motivations, Frustrations, and Design Opportunities,” first delivered as a paper at the 2017 ACM (Association for Computing Machinery) conference. It explored the experiences of adults aged 60 years or older who sought to learn to code by taking Internet-based online classes at Python Tutor. A survey found most of the students were employed in STEM occupations. It also considered reasons to pursue education, frustrations, and learning frameworks.